Joseph I, “The Regenerative King”. The Josefino’s Speech on the Regeneration of Spain - Piqueres Díez, Antonio J. (Cuadernos de Historia Moderna, 2012)
The Napoleonic invasion of Spain in 1808 supposed one of the most turbulent periods in its history. The abdications in the Bourbon family and Joseph Bonaparte’s enthronement exacerbated the minds of Spaniards. Within this context of war, however, Joseph I undertook an ambitious reform plan to regenerate the monarchy. Politics, the economy, and the education were some of the renewed areas. Joseph’s propaganda service, largely controlled by Napoleon, soon spread a legitimizing image of Joseph I as “King regenerator”. Part of the same strategy consisted in criticizing the Bourbon’s management; however, the response of the anti-Bonapartist propaganda and, mainly, the distrust of the people frustrated Joseph’s plans.